Evidence of the influence of digital marketing on the motivation towards purchase in the service sector in Latin America, 2019- 2021 - Estrada-Luyo, Marioti Antoanet; Fernández-Bedoya, Víctor Hugo (LACCEI, 2023)
The objective of this research was to gather evidence on the influence of digital marketing on the motivation towards purchase in the service sector in Latin America, 2019- 2021. The information questions were formulated: what are the evidences of the influence of digital marketing on the motivation towards purchase in the service sector in Latin America, 2019- 2021? Which countries do they come from, in which scientific journals or academic repositories were they published? What research approaches did they employ? And finally, what conclusions and results did they have? The research approach was qualitative, the level was exploratory, retrospective longitudinal nonexperimental design. The databases "La Referencia", "Redalyc", "ScienceDirect", "Scielo", "Google Scholar", "Proquest", "EBSCO Host", and "Gate Academic One File" were explored. Six scientific evidences were identified. The country where the records came from was Peru (six cases). The repository where most of the theses or articles came from was the Universidad César Vallejo (four cases). Regarding the research approach, most of them were quantitative (five cases). In general terms, it is possible to affirm that digital marketing has an influence on purchase motivation in the service sector in several cases observed in Latin America.